Biofertilizer Production using Phosphate-solubilizing Pseudomonas spp. Isolated from Rhizosphere Soil: Towards Indigenous Biofertilizer for Enhanced Crop Productivity in Katsina, Nigeria - Sani Isiya; Baha'uddeen Salisu (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt